On New Generalized Hybrid Synchronization in Chaotic and Hyperchaotic Discrete-time Dynamical Systems - Ouannas, Adel; Jouini, Lotfi; Zehrour, Okba (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, by combining full state hybrid projective synchronisation (FSHPS) and inverse full state hybrid projective synchronisation (IFSHPS), we generalize the idea of hybrid chaos synchronization in discrete-time. Based on stability theory of linear discrete-time systems and Lyapunov stability theory, new approaches are proposed to investigate the new type of hybrid synchronization between chaotic maps of diﬀerent dimensions. Several numerical examples have highlighted the eﬀectiveness of the novel approaches developed herein.